Optimalisasi Peran Guru Bimbingan dan Konseling melalui Cognitive Behavior Stress Management untuk Mendukung Peer Counselor dalam Penanggulangan Stres Akademik Siswa - Khairul Bariyyah; Adi Atmoko; Ella Faridati Zen; Rizka Apriani; Nining Maizura (Abdimas Pedagogi: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Abstract: This community service project aims to evaluate the implementation of Cognitive Behavior Stress Management (CBSM) by school counselor in supporting peer counselors as part of efforts to mitigate students’ academic stress in junior high schools (MTS). CBSM is an approach that combines Cognitive Behavioral Therapy (CBT) techniques and stress management, designed to help students more effectively manage academic pressures. In this study, 25 school counselor participated in CBSM training and served as facilitators to train peer counselors at their respective schools. The evaluation results indicate that the CBSM training provided clear and relevant understanding for school counselor and peer counselors. The training significantly enhanced peer counselors' practical skills in identifying and managing academic stress symptoms in students. CBSM implementation was found effective in fostering a more positive school climate, increasing social support among students, and strengthening the role of peer counselors in addressing mental health issues. With ongoing support from school counselor, CBSM also positively impacted students' emotional and academic well-being. Recommendations from this study include increasing the frequency of CBSM training and providing regular guidance for peer counselors to reinforce the long-term effectiveness of this program. Abstrak: Pengabdian masyarakat ini bertujuan untuk mengevaluasi implementasi Cognitive Behavior Stress Management (CBSM) oleh guru Bimbingan dan Konseling (BK) dalam mendukung peer counselor sebagai upaya penanggulangan stres akademik siswa di sekolah menengah pertama (MTS). CBSM merupakan pendekatan yang menggabungkan teknik-teknik Cognitive Behavioral Therapy (CBT) dan manajemen stres yang dirancang untuk membantu siswa mengelola tekanan akademik dengan lebih efektif. Dalam studi ini, 25 guru BK mengikuti pelatihan CBSM dan berperan sebagai fasilitator untuk melatih peer counselor di sekolah masing-masing. Hasil evaluasi menunjukkan bahwa pelatihan CBSM memberikan pemahaman yang jelas dan relevan bagi para guru BK dan peer counselor. Pelatihan ini secara signifikan meningkatkan keterampilan praktis peer counselor dalam mengidentifikasi serta mengelola gejala stres akademik pada siswa. Implementasi CBSM dinilai efektif dalam menciptakan iklim sekolah yang lebih positif, meningkatkan dukungan sosial antar siswa, dan memperkuat peran peer counselor sebagai pendamping dalam penanganan masalah mental. Dengan adanya dukungan guru BK yang berkelanjutan, CBSM juga memberikan dampak positif terhadap kesejahteraan emosional dan akademik siswa. Rekomendasi penelitian ini mencakup peningkatan frekuensi pelatihan CBSM dan bimbingan berkala bagi peer counselor untuk memperkokoh efektivitas program ini dalam jangka panjang.